Cloning of miR319b precursor gene and expressing analysis during the in vitro plantlets development by qPCR in Amaranthus tricolor L - Liu, Shengcai; Kuang, Huaqin; Xie, Liyang; Lai, Zhongxiong (Zhejiang da xue xue bao. Journal of Zhejiang University. Sciences edition. Li xue ban, 2014)
In vitro plantlets and the cultures during the in vitro plantlets development were used as the materials to clone miR319b precursor by RT-PCR, and its expression level during the in vitro plantlets development in Amaranthus tricolor L was conducted by qPCR. The results show that miR319b precursor is 186 bp in length, including 21 bp mature sequence of miR319b. Meanwhile the miR319b precursor of Amaronthus tricolor L shows high sequence homology with that from Nicotiana tabacum and Medicago sativa. With qPCR, we can find that the relative expression level of ama-miR319b is the lowest at the young seedling stage, then up-regulated at the adult seedling stage and the flower-bud stage. It is highest at flower-bud stage, then is decreased. The relative expression level at flowering stage is slightly higher than that at adult seedling stage. Therefore, the miR319b precursor perhaps plays the important role in regulating the conversion from the young seedling stage to the adult seedling stage, as well as from the ve